Covid-19 and Unemployment: Evidence from Puerto Rico Using Bayesian Analyses with High-Frequency Data - Toledo, Wilfredo (Economics and Business, 2021)
The paper aims at determining the relationship between the Covid-19 contagion level and the state of the economy using high-frequency data from Puerto Rico. In order to achieve the aim set, the direction of the causality relationship between the numbers of infected persons and the unemployment rate was determined. Furthermore, various Bayesian statistical models were estimated. The analysis results imply that the unemployment rate responds moderately to the Covid-19 contagion level itself and not the other way around. The 95 % credible interval for the elasticity coefficient of the unemployment rate relative to the virus is estimated as [0.0140–0.1448]. Evidence also shows that at the beginning of 2021, most of the fluctuations in the unemployment rate were explained directly by the Covid-19 perturbations. Hence, no evidence was found that economic activity promoted the virus spread in the analysed economy.